Gen Z Sehat Kenali Bahaya Vape, Seks Bebas, Penyalahgunaan Obat di SMA Negeri 3 Lamongan - Djati Wulan Khusumo; Andre Situmeang; Aprilia Suryan Dini; Eka Wulan Ndari; Lifriana Zahwa Nabila (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
This community service activity aimed to improve students’ knowledge and awareness regarding the dangers of vaping, free sex, and drug abuse among adolescents. The activity was conducted at SMAN 3 Lamongan on April 13, 2026, involving 28 students. The implementation method consisted of health counseling through material presentation using presentation media, interactive discussions, and evaluation using pretest and posttest methods. The materials covered the dangers of vaping and smoking, risky sexual behavior, and drug abuse. The results showed an increase in students’ knowledge after the counseling session. The average pretest score was 84.24%, which increased to 98.57% in the posttest. The Wilcoxon test result showed a significance value of 0.000 (<0.05), indicating a significant difference between pretest and posttest scores. This demonstrates that health education was effective in improving students’ knowledge related to healthy lifestyles and prevention of risky behaviors. Therefore, this activity is expected to serve as a promotive and preventive effort in shaping a healthy young generation that is aware of the importance of maintaining personal health